Single-cell genomics for dissection of complex malaria infections - Nair, Shalini; Nkhoma, Standwell C.; Serre, David; Zimmerman, Peter A.; Gorena, Karla; Daniel, Benjamin J.; Nosten, François; Anderson, Timothy J.C.; Cheeseman, Ian H.

(untitled) (Genome Research, 2014)
Most malaria infections contain complex mixtures of distinct parasite lineages. These multiple-genotype infections (MGIs) impact virulence evolution, drug resistance, intra-host dynamics, and recombination, but are poorly understood. To address this we have developed a single-cell genomics approach to dissect MGIs. By combining cell sorting and whole-genome amplification (WGA), we are able to generate high-quality material from parasite-infected red blood cells (RBCs) for genotyping and next-generation sequencing. We optimized our approach through analysis of >260 single-cell assays. To quantify accuracy, we decomposed mixtures of known parasite genotypes and obtained highly accurate (>99%) single-cell genotypes. We applied this validated approach directly to infections of two major malaria species, Plasmodium falciparum, for which long term culture is possible, and Plasmodium vivax, for which no long-term culture is feasible. We demonstrate that our single-cell genomics approach can be used to generate parasite genome sequences directly from patient blood in order to unravel the complexity of P. vivax and P. falciparum infections. These methods open the door for large-scale analysis of within-host variation of malaria infections, and reveal information on relatedness and drug resistance haplotypes that is inaccessible through conventional sequencing of infections.